Allegiance and knowledge levels of professionals working with early intensive behavioural intervention in autism. Issue 5 (6th April 2016) - Långh, Ulrika; Hammar, Martin; Klintwall, Lars; Bölte, Sven
Abstract: Aim: Early intensive behavioural intervention (EIBI) for children with autism spectrum disorder (ASD) is often delivered using a community model. Behaviour modification experts train and supervise non‐experts (e.g. preschool personnel) to teach children according to applied behaviour analysis principles in their natural environment. Several factors predict EIBI outcomes in ASD, for example, knowledge of EIBI and EIBI allegiance among trainers. The aim of the present study was to survey levels of knowledge about and allegiance towards EIBI. Methods: Formal knowledge of EIBI and EIBI allegiance was surveyed in supervised preschool staff conducting EIBI ( n = 33), preschool staff not involved in EIBI ( n = 26), behaviour modification experts ( n = 60), school staff ( n = 25) and parents of children with ASD ( n = 150) [ N = 294]. A 27‐item (15 knowledge and 12 allegiance questions) online questionnaire was collected. Results: Supervised preschool staff conducting EIBI had more knowledge than preschool staff not using EIBI, but they were not more allegiant. Compared with behaviour modification experts, the supervised EIBI preschool staff group showed markedly less knowledge and allegiance. Conclusions: Findings indicate potential for improvement regarding formal knowledge levels of preschool staff delivering EIBI to children with ASD in real‐world settings. In addition, fostering EIBI allegiance might be prioritized when teaching EIBI among non‐experts. Broadly increased EIBI knowledge levels among all preschool teachers should be achieved by adding behaviour modification techniques to common university curricula in preschool education. Allegiance of preschool personnel might be accomplished by EIBI supervisors meeting skepticism in practice with conveyance of evidence‐based principles and discussions of ethical issues.